2018
DOI: 10.1021/acs.jpclett.8b02734
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Chirality-Selective Photoluminescence of Single-Walled Carbon Nanotubes by Ionic Liquids

Abstract: The chirality-selective near-infrared emission of surfactant-stabilized single-wall carbon nanotubes could be controlled by simply varying the anion of the commonly used 1-butyl-3-methylimidazolium ionic liquids. This result advances the notion of the designer solvent ability of ionic liquids and provides opportunities for modulating the properties of nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…In turn, charge transport is governed by charge-scattering processes, among which electron–phonon scattering constitutes the main mechanism of charge and energy losses to heat. Multiple time-resolved spectroscopic experiments and a few simulations have been carried out in order to characterize charge scattering in CNTs and GNRs, including both carrier–carrier and carrier–phonon scattering. It has been demonstrated that energetic charge carriers in CNTs couple to the high-frequency G-modes, while charges with lower energies couple to lower-frequency radial breathing (RBM) vibrations. Atomic and boundary defects, as well as CNT ends, are known to contribute significantly to nonradiative charge–phonon relaxation, because CNTs are very good conductors and charges can easily reach defect sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, charge transport is governed by charge-scattering processes, among which electron–phonon scattering constitutes the main mechanism of charge and energy losses to heat. Multiple time-resolved spectroscopic experiments and a few simulations have been carried out in order to characterize charge scattering in CNTs and GNRs, including both carrier–carrier and carrier–phonon scattering. It has been demonstrated that energetic charge carriers in CNTs couple to the high-frequency G-modes, while charges with lower energies couple to lower-frequency radial breathing (RBM) vibrations. Atomic and boundary defects, as well as CNT ends, are known to contribute significantly to nonradiative charge–phonon relaxation, because CNTs are very good conductors and charges can easily reach defect sites.…”
mentioning
confidence: 99%
“…In particular, Bonn and co-workers measure time-resolved photoconductivity of CNTs and GNRs and show that electron–phonon scattering events are more frequent in GNRs, and as a result, the conductivity decays several times faster in GNRs than CNTs. These as well as many other time-resolved experiments are most closely mimicked by nonadiabatic (NA) molecular dynamics (MD) techniques, developed initially in the 1960s and 1970s to study gas-phase and surface scattering processes and adapted later to condensed-phase systems. Our group developed several NAMD approaches designed specifically for nanoscale systems and implemented them within time-dependent density functional theory (TDDFT). …”
mentioning
confidence: 99%
“…It was previously shown that certain ssDNA-SWCNT combinations exhibit chirality-dependent responses upon molecular recognition. [56,[58][59][60][61] Moreover, several DNA sequences were shown to preferentially bind one handedness, [56] which can in turn affect the fluorescence response to one enantiomer over the other. In our study, some SWCNT chiralities [(9,5), (8,7), (6,5)] were more responsive than others when suspended with (ATTT) 7 , hinting a possible chirality dependence of the sensor, which might contribute to the obvious distinction between the enantiomers D2HG and L2HG.…”
Section: Screeningmentioning
confidence: 99%